Pengembangan Media Pembelajaran Video Animasi Cerita Rakyat Untuk Meningkatkan Kemampuan Memirsa Siswa Kelas IV SDI Ma'arif Garum - Laylatul Afifah; Isna Khuni Mualimah; Ragil Tri Oktaviani (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Viewing skill is among the key language competencies that students must develop within the framework of Indonesia's Merdeka Curriculum. A preliminary study conducted at SDI Ma'arif Garum, however, found that fourth-grade students had not adequately developed this skill, largely due to the dominance of teacher-centered learning approaches and the absence of varied instructional media. In response to this gap, the present study sought to design and evaluate an animated video learning medium grounded in the local Blitar folklore of Bubuksah and Gagang Aking. The research adopted a Research and Development (R&D) approach guided by the ADDIE framework, which encompasses five sequential phases: Analyze, Design, Development, Implementation, and Evaluation. Validation involved a panel of subject matter specialists, media technologists, and language reviewers, as well as classroom practitioners and fourth-grade learners as end users. Data collection relied on observation, in-depth interviews, validation instruments, documentation records, and viewing skill assessments, with quantitative data analyzed descriptively and media effectiveness evaluated through a One-Sample t-Test using IBM SPSS Statistics. Expert validation yielded feasibility ratings of 94% from content validators, 92% from media evaluators, and 95% from language reviewers — all categorized as highly valid. Student performance data further demonstrated a meaningful learning gain, with average scores climbing from 60.00 at the pre-test stage to 90.50 following media implementation. These findings confirm that the animated video based on the Bubuksah and Gagang Aking folklore constitutes an effective, engaging, and contextually appropriate medium for enhancing elementary students' viewing skills, learning engagement, and comprehension of folk narrative content.